Rancangan Sistem Informasi Surat Masuk Dan Surat Keluar Berbasis Web Di Kecamatan Bontang Barat - Layuk, Lapu Tombi; Annisa Hashifah Rahmah (Jurnal Teknik Juara Aktif Global Optimis, 2023)
The West Bontang District Office is still experiencing difficulties in managing incoming and outgoing mail such as recording incoming and outgoing mail data such as date of receipt, date of sending, date of letter, letter number, type of letter, recipient, disposition of letter. This management still uses manual work procedures, namely using ledgers and Microsoft Excel in making daily agendas. A website-based data management system is the choice because it can facilitate access to information, besides that this technology can help manage incoming and outgoing letters properly, and optimize the recording time and disposition of letters. The system development method uses the waterfall method and is built using the PHP programming language and MySQL database. The end result of this research is a web-based information system for Incoming Mail and Outgoing Mail that can minimize recording errors and data loss, and can assist employees in storing mail archive data to match the type.